Competition, Concentration and Percentage Rent in Retail Leasing. (21st May 2019) - Guven, Gokhan; Inci, Eren; Russo, Antonio
Abstract: Competing retailers benefit from concentrating under a shopping mall because more consumers visit the mall to economize on search costs. Consumers would also benefit from concentration if retailers cut prices to attract more of the incoming consumers. We show that such competition may be only apparent because the mall alleviates competition among retailers. Although consumers have rational expectations about the price levels at the mall, they learn the exact prices and features of goods only after visiting the mall. In addition to the usual fixed rent, most rental lease contracts at malls require retailers to pay a percentage rent that increases with sales revenue. The mall uses the percentage rent to keep the prices charged by competing retailers high, which increases retailers' joint revenue. It then charges the fixed rent to extract surplus from them. Hence, as long as prices are not perfectly observable, concentration results in higher prices.